Carbohydrate supplementation and psychophysiological responses during moderate exercise in hypoxia - Tavares-Silva, E. (J Int Soc Sports Nutr, 2020)
BACKGROUND: Rating of Perceived Exertion (RPE) is a subjective scale to monitor overload and fatigue during exercise. Hypoxia may worsen the perception of fatigue, compromising the self-reported perception of effort and increasing RPE. The objective was to evaluate the effects of carbohydrate (CHO) supplementation on RPE during exercise in hypoxia simulating 4200 m. METHODS: Eight male physically active volunteers performed two exercises at 50% VO(2peak) and 1% slope: exercise in hypoxia + placebo or exercise in hypoxia + CHO (6% maltodextrin) with supplementation at 20, 40, and 60 min during exercise. Oxygen Saturation (SaO(2)%) was assessed at baseline and after exercise, while RPE and HR were measured each 10 min during the trial. RESULTS: SaO(2)% decreased after exercise in both conditions of hypoxia compared to rest. The RPE did not differ between groups. However, the RPE increased in hypoxia after 20 min of exercise in relation to 10 min. The Area Under the Curve (AUC) of RPE was lower in hypoxia + CHO compared to hypoxia. The AUC of the HR/RPE ratio in the hypoxia + CHO group was higher in relation to hypoxia. CONCLUSIONS: Our results indicate that CHO supplementation does not change RPE induced by 60 min of exercise at 50% VO(2peak) in hypoxia equivalent to 4200 m at the different times analyzed. However, in hypoxia + CHO the (AUC)-60 min of total RPE decreased during exercise, while the heart rate/RPE ratio improved, indicating lower RPE in the hypoxic environment.